2012
DOI: 10.1007/s00221-012-3135-3
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlates of after-effects caused by adaptation to multiple face displays

Abstract: Adaptation to a given face leads to face-related, specific after-effects. Recently, this topic has attracted a lot of attention because it clearly shows that adaptation occurs even at the higher stages of visual cortical processing. However, during our every-day life, faces do not appear in isolation, rather they are usually surrounded by other stimuli. Here, we used psychophysical and fMRI adaptation methods to test whether humans adapt to the gender properties of a composite multiple face stimulus as well. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 86 publications
1
6
0
Order By: Relevance
“…To recognize ensemble facial expressions, unlike gender, it is necessary to assess the shapes of multiple facial parts and combine the information. Our results indicate that an ensemble average of facial expressions could be extracted from facial expressions presented simultaneously; thus, our findings are consistent with those of a previous study investigating gender (Nagy et al, 2012 ). In the ensemble conditions, the intensities of the individual facial expressions differed from their average intensity.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…To recognize ensemble facial expressions, unlike gender, it is necessary to assess the shapes of multiple facial parts and combine the information. Our results indicate that an ensemble average of facial expressions could be extracted from facial expressions presented simultaneously; thus, our findings are consistent with those of a previous study investigating gender (Nagy et al, 2012 ). In the ensemble conditions, the intensities of the individual facial expressions differed from their average intensity.…”
Section: Discussionsupporting
confidence: 93%
“…Nagy et al ( 2012 ) demonstrated that adaptation to the gender of individual faces presented simultaneously distorted gender discrimination performance of a face subsequently presented; participants perceived an ambiguous test face as more masculine after adaptation to a female facial set and vice versa. The results were consistent with those of previous studies that used a single female or male face as adaptation stimuli (Kovács et al, 2008 ; Webster et al, 2004 ).…”
mentioning
confidence: 99%
“…For example, in a case where a few display extremely strong positive expressions and others show slightly negative expressions, the average of their expressions is relatively positive. Therefore, average perception does not necessarily lead to a correct answer to majority judgment considering the number and intensity (see Nagy, Zimmer, Greenlee, & Kovács, 2012). Although counting the items is the best strategy, it is impractical as counting items at a glance is difficult, except for a small number of items (Kaufman et al, 1949).…”
mentioning
confidence: 99%
“…The specific contribution of enumeration or majority search in processing multiple facial expressions remains to be fully elucidated and should be carefully controlled in future studies, including using specific control analyses as carried out here. For example, this could be achieved by manipulating both the ratio of different kinds of expressions and the mean intensity of faces in the set (e.g., the average emotion is more positive even when there are more negative faces in the set), such as previously done in a study focusing on gender processing (Nagy, Zimmer, Greenlee, & Kovács, 2012).…”
Section: Discussionmentioning
confidence: 99%